Incidence and risk factors of postoperative delirium in patients admitted to the ICU after elective intracranial surgery: A prospective cohort study. Issue 1 (January 2020) - Wang, Chun-Mei; Huang, Hua-Wei; Wang, Yu-Mei; He, Xuan; Sun, Xiu-Mei; Zhou, Yi-Min; Zhang, Guo-Bin; Gu, Hong-Qiu; Zhou, Jian-Xin
Abstract : BACKGROUND: Postoperative delirium (POD) has been confirmed as an important complication after major surgery. However, neurosurgical patients have usually been excluded in previous studies. To date, data on POD and risk factors in patients after intracranial surgery are scarce. OBJECTIVES: To determine the incidence and risk factors of POD in patients after intracranial surgery. DESIGN: Prospective cohort study. SETTING: A neurosurgical ICU of a university-affiliated hospital, Beijing, China. INTERVENTIONS: Adult patients admitted to the ICU after elective intracranial surgery under general anaesthesia were consecutively enrolled between 1 March 2017 and 2 February 2018. Delirium was assessed using the Confusion Assessment Method for the ICU. POD was diagnosed as Confusion Assessment Method for the ICU positive on either postoperative day 1 or day 3. Patients were classified into groups with or without POD. Data were collected for univariate and multivariate analyses to determine the risk factors for POD. RESULTS: A total of 800 patients were included. POD was diagnosed in 157 patients (19.6%, 95% confidence interval 16.9 to 22.4%). Independent risk factors for POD included age, nature of intracranial lesion, frontal approach craniotomy, duration of surgery, presence of an episode of low pulse oxygenation at ICU admission, presence of inadequate emergence and emergence delirium, postoperative pain and presence of immobilising events. POD was associated with adverse outcomes and high costs. CONCLUSION: POD is prevalent in patients after elective intracranial surgery. The identified risk factors for and the potential association of POD with adverse outcomes suggest that a comprehensive strategy involving screening for predisposing factors and early prevention of modifiable factors should be established in this population. TRIAL REGISTRATION: ClinicalTrials.gov NCT03087838. Abstract : Supplemental Digital Content is available in the text